Are polymer-based burs smart enough to remove infected dentin compared to tungsten carbide burs? - Saad Shahnawaz,; Muhammad Muhammad,; Amber Kiyani,; Alia Ahmed, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To compare the efficiency of smart burs during cavity preparation compared to tungsten carbide burs in removing infected dentin. Methodology: This study was experimental and survey design used. The 60 freshly extracted teeth were equally divided into the smart bur group and the tungsten carbide bur group. Each tooth cavity preparation was done at 5000rpm with a slow-speed handpiece under water irrigation. After cavity preparation, the teeth were trimmed, sectioned, and introduced on the slide with hematoxylin and eosin gram staining to identify the presence or absence of bacteria in the dentinal tubules. Results: A statistically significant difference at a p-value of .002 was calculated between Carbide burs being more effective in infected dentin removal compared to smart burs.a majority of sections, precisely 22 sections out of the total analyzed (constituting 84.6%), exhibited discernible evidence of infected dentin, characterized by the conspicuous presence of bacterial colonies within the dentinal tubules upon microscopic examination. However, a limited number of sections, specifically 4 sections (constituting 15.4% of the sample), posed challenges for the histopathologist in providing a conclusive assessment regarding the presence or absence of organisms Conclusion: Smart burs were unable to completely remove carious infected dentin of the prepared tooth cavities compared to carbide burs. Keywords:Smartburs,conservative cavity preparation,infected dentin,affected dentin